Changes in Gene Expression in Space and Time Orchestrate Environmentally Mediated Shaping of Root Architecture. Issue 10 (11th September 2017) - Walker, Liam; Boddington, Clare; Jenkins, Dafyd; Wang, Ying; Grønlund, Jesper T.; Hulsmans, Jo; Kumar, Sanjeev; Patel, Dhaval; Moore, Jonathan D.; Carter, Anthony; Samavedam, Siva; Bonomo, Giovanni; et al.
Abstract : Tracking cell-type transcriptomic responses to treatments that change root development at an unprecedented level of temporal detail reveals molecular mechanisms that shape root architecture. Abstract: Shaping of root architecture is a quintessential developmental response that involves the concerted action of many different cell types, is highly dynamic, and underpins root plasticity. To determine to what extent the environmental regulation of lateral root development is a product of cell-type preferential activities, we tracked transcriptomic responses to two different treatments that both change root development in Arabidopsis thaliana at an unprecedented level of temporal detail. We found that individual transcripts are expressed with a very high degree of temporal and spatial specificity, yet biological processes are commonly regulated, in a mechanism we term response nonredundancy. Using causative gene network inference to compare the genes regulated in different cell types and during responses to nitrogen and a biotic interaction, we found that common transcriptional modules often regulate the same gene families but control different individual members of these families, specific to response and cell type. This reinforces that the activity of a gene cannot be defined simply as molecular function; rather, it is a consequence of spatial location, expression timing, and environmental responsiveness.